2021
DOI: 10.2217/pgs-2021-0142
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Including African Populations in Pharmacogenetics Studies of Warfarin Response

Abstract: Tweetable abstract Warfarin will remain in use for a long time to come, thus inclusion of African populations in pharmacogenomics is essential to be able to identify all possible biomarkers that are potential predictors for warfarin drug response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This has called for the need for better, more efficient, and cost-effective solutions to manage hypertension and pharmacogenetics has a potential of integrating all these solutions. However, the mammoth challenge is that there are currently limited pharmacogenetic studies in African populations focussing on hypertension and therefore the potential of pharmacogenetics cannot be fully harnessed as studies are few to bridge the gap between clinical implementations of pharmacogenetics [ 137 , 138 ].…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has called for the need for better, more efficient, and cost-effective solutions to manage hypertension and pharmacogenetics has a potential of integrating all these solutions. However, the mammoth challenge is that there are currently limited pharmacogenetic studies in African populations focussing on hypertension and therefore the potential of pharmacogenetics cannot be fully harnessed as studies are few to bridge the gap between clinical implementations of pharmacogenetics [ 137 , 138 ].…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…In other parts of the world, where pharmacogenetic implementation studies have been carried out, clinicians have reported improved clinical outcomes in patients who had undergone pharmacogenetic testing prior [38,[142][143][144]. As a result, dosing algorithms for drugs/drug classes such as clopidogrel, tamoxifen, and warfarin/statins [145][146][147], have now been developed for Europeans and Asians and these are now gaining momentum in Africa, with promising potential for implementation, as more data are being generated for native and admixed African populations [43,46,47,138,148,149]. For hypertension, only metoprolol has dosing guidelines based on CYP2D6 genotypes proposed by the DPWG.…”
Section: Presenting a Case For Africa And Concluding Remarksmentioning
confidence: 99%
“…Furthermore, the Hispanics are an admixed population of Europeans, Native American and West-Africans (Bryc et al, 2010;Baran et al, 2012) and therefore extrapolating the findings of PGx studies conducted among Europeans to such an admixed population carries the risk of undermining the validity of any evidence that supports the implementation of PGx and precision medicine and remains a flawed practice (Ramos et al, 2012;Claudio-Campos et al, 2015;Grinde et al, 2019;Lee et al, 2019). Similarly, findings from the few studies conducted among AAs should not be directly extrapolated to other black populations such as sub-Saharan Africans or Afro-Brazilians given that the genetic architecture of AAs is distinct from that of other Africans (Zakharia et al, 2009;Dandara et al, 2022). Moreover, the development of therapeutics relies on evidence from clinical trials conducted mainly in non-Hispanic Whites or less frequently among Asian populations.…”
Section: Pgx and Implications Of Genetic Ancestrymentioning
confidence: 99%
“…While DOACs have become the standard of care for patients with deep vein thrombosis compared to Vitamin K antagonists, low-income and black patients consistently receive less prescriptions of DOACs even when they are insured ( Nathan et al, 2019 ). Similarly, utilization of DOACs remain limited in African countries due to its unaffordability because of patent laws, in addition to lack of clinical trials to address its safety in African populations ( Semakula et al, 2021 ; Dandara et al, 2022 ). With a growing body of studies of DOACs PGx, efforts to enroll minorities, which most probably would also fall on a lower level of SES, is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%